Utilization of liquid organic fertilizer coffee (Coffea arabica L.) as a hydroponic nutrition in pakcoy (Brassica rapa L.) - Ayu Adelia; Violita Violita (Bioscience, 2022)
Pakcoy (Brassica rapa L.) is a type of vegetable plant that belongs to the Brassicaceae family. Content contained in Pakcoy are calories, protein, fat, carbohydrates, fiber, Ca, P, Fe, vitamins A, vitamins B and vitamins C. The high demand for vegetables, especially Pakcoy, is not matched by the extent of agricultural land for farming. One of the solutions that can be used for the cultivation of Pakcoy plants is hydroponically which does not require a large area of land, can also be done in the yard or terrace of the house. Coffe grounds can be used as organic fertilizer in a hydroponic system and can be an alternative that can be used to replace inorganic fertilizers. This study uses a CRD (Completely Randomized Design) with treatments consisting of 5 levels: A1B1 (1 dose AB Mix), A2B2 (½ dose AB Mix+5 mL liquid organic fertilizer coffe grounds), (½ dosis AB Mix+10 mL liquid organic fertilizer coffe grounds), (5 mL liquid organic fertilizer coffe grounds) and (10 mL liquid organic fertilizer coffe grounds). The result showed that the provision of hydroponic nutrients of coffe grounds\had an effect on the growth of Pakcoy, but the growth was lower than that of AB Mix.Pakcoy (Brassica rapa L.) merupakan salah satu jenis tanaman sayuran yang termasuk dalam famili Brassicaceae. Kandungan yang terkandung di dalam pakcoy adalah kalori, protein, lemak, karbohidrat, serat, Ca, P, Fe, vitamin A, vitamin B dan vitamin C. Tingginya permintaan sayuran khususnya pakcoy tidak diimbangi dengan luasnya lahan pertanian untuk bercocok tanam. Salah satu solusi yang bisa digunakan untuk budidaya tanaman pakcoy adalah secara hidroponik yang tidak membutuhkan lahan yang luas, bisa juga dilakukan di pekarangan atau teras rumah. Ampas kopi dapat digunakan sebagai pupuk organik dalam sistem hidroponik dan dapat menjadi alternatif yang dapat digunakan untuk menggantikan pupuk anorganik. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) dengan perlakuan yang terdiri dari 5 taraf : A1B1 (1 dosis AB Mix), A2B2 (½ dosis AB Mix+5 mL pupuk organik cair ampas kopi), (½ dosis AB Mix+10 mL cair pupuk organik ampas kopi), (5 mL pupuk organik cair ampas kopi) dan (10 mL pupuk organik cair ampas kopi). Hasil penelitian menunjukkan bahwa pemberian nutrisi hidroponik ampas kopi berpengaruh terhadap pertumbuhan Pakcoy, namun pertumbuhannya lebih rendah dibandingkan dengan AB Mix.